A novel transposon, Tn6306, mediates the spread of blaIMI in Enterobacteriaceae in hospitals. (December 2017) - Zhang, Fangfang; Wang, Xiaoli; Xie, Lianyan; Zheng, Qiuyue; Guo, Xiaokui; Han, Lizhong; Sun, Jingyong
Highlights: The molecular characteristics of IMI-3-producing plasmid RJ46C and IMI-2-producing plasmid RJ18 were analyzed. The novel transposon Tn 6306, and other insert sequences, may play important roles in bla IMI mobilization. The identification of blaIMI in R. ornithinolytica and E. coli highlights the diversity of spreading carbapenemases in Enterobacteriaceae between hospitals and the environment in China. Abstract: The increasing incidence of carbapenem-resistant Enterobacteriaceae has become a challenge for clinical therapy. In our study, we analysed the molecular characteristics of imipenem-hydrolyzing β-lactamase (IMI) in Enterobacteriaceae isolates. Two reported clinical isolates, the IMI-3-producing Raoultella ornithinolytica RJ46C and the IMI-2-producing Escherichia coli RJ18 were identified in our retrospective review of isolates collected from June 2010 to June 2013, both isolates were resistant to carbapenem but sensitive to expanded-spectrum cephalosporins. The bla IMI gene was located on different ∼170-kb plasmids in both isolates. The bla IMI-3 gene was carried by the plasmid pRJ46C, which was extracted from the transconjugant and identified to be a 166, 620-bp conjugative IncFIIY plasmid that contained 193 open reading frames, including replication-, plasmid conjugal transfer-, partitioning-, and mobilization-associated structures. The bla IMI-3 gene was located on a 15-kb region with a completely inverted sequence relative to that of plasmid pGA45, two IS Ecl1 -like elements containing two 33-bp complete inverted repeats were in an inverted orientation on both sides of the 15-kb region. We identified this typical structure as a novel composite transposon named Tn 6306, indicating the occurrence of transposition. In addition, the bla IMI-2 -carrying pRJ18 was an IncFIB plasmid, and a similar IS Ecl1 -like element was identified in an inverted direction upstream of IMI-2 in pRJ18. The identification of bla IMI in R. ornithinolytica and E. coli highlights the diversity of spreading carbapenemases in Enterobacteriaceae between hospitals and the environment in China. The novel transposon Tn 6306, and other insert sequences, may play important roles in bla IMI mobilization.